Evaluation of Disulfiram Drug Combinations and Identification of Other More Effective Combinations against Stationary Phase Borrelia burgdorferi - Hector S. Alvarez-Manzo; Yumin Zhang; Wanliang Shi; Ying Zhang (MDPI AG, 2020)
Lyme disease, caused by Borrelia burgdorferi, is the most common vector-borne disease in USA, and 10-20% of patients will develop persistent symptoms despite treatment ("post-treatment Lyme disease syndrome"). B. burgdorferi persisters, which are not killed by the current antibiotics for Lyme disease, are considered one possible cause. Disulfiram has shown to be active against B. burgdorferi, but its activity against persistent forms is not well characterized. We assessed disulfiram as single drug and in combinations against stationary-phase B. burgdorferi culture enriched with persisters. Disulfiram was not very effective in the drug exposure experiment (survival rate (SR) 46.3%) or in combinations. Clarithromycin (SR 41.1%) and nitroxoline (SR 37.5%) were equally effective when compared to the current Lyme antibiotic cefuroxime (SR 36.8%) and more active than disulfiram. Cefuroxime + clarithromycin (SR 25.9%) and cefuroxime + nitroxoline (SR 27.5%) were significantly more active than cefuroxime + disulfiram (SR 41.7%). When replacing disulfiram with clarithromycin or nitroxoline in three-drug combinations, bacterial viability decreased significantly and subculture studies showed that combinations with these two drugs (cefuroxime + clarithromycin/nitroxoline + furazolidone/nitazoxanide) inhibited the regrowth, while disulfiram combinations did not (cefuroxime + disulfiram + furazolidone/nitazoxanide). Thus, clarithromycin and nitroxoline should be further assessed to determine their role as potential treatment alternatives in the future.